Economic Science Fictions - Davies, William (PERC, 2019)
From the libertarian economics of Ayn Rand to Aldous Huxley's consumerist dystopias, economics and science fiction have often circled each other's spheres. In Economic Science Fictions, editor William Davies has deliberately merged the two worlds, asking how we might harness the power of the utopian imagination to revitalise economic thinking.